Study of the Cashew Nut Product Processing Process at UD. Cashew Mubaraq Kendari City - Kiki, Wa Ode; Herdhiansyah, Dhian; Abdulllah, Weka Gusmiarty; Asriani, Asriani (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2024)
AThis research aims to determine the cashew product processing process at UD. Cashew Mubaraq in Kendari City. Data collection was carried out using interview and documentation methods. The analysis used is descriptive analysis. Based on the research results, it is shown that the cashew product processing process at UD. Cashew Mubaraq in Lombe begins with the stages: (a) providing raw materials, (b) washing process, (c) process of providing flavorings, (d) frying process, (e) process of adding flavorings, and (f) packaging process. Production activities carried out by UD. Mete Mubaraq Lombe are done 8 times a month. The production volume for each month can process 40 tonnes of cashew nuts with the assumption of 8 tonnes of peeled cashews with a sales volume of 4 tonnes of raw cashews (super and regular), 3.5 tonnes of fried cashews, and 0.5 tonnes of cashew shells. This production can increase when there is an increase in market demand.